Designing Character for Bandung Tourism Campaign - Devi Kurniawati Homan; Aris Darisman (Bina Nusantara University, 2017)
Bandung is the capital of west java province in Indonesia. It was referred to Paris van Java because of the beauty. Nowadays, since access to the city of Bandung is easier both domestically and international, Bandung become the travel destination. Like other travel destination in Indonesia, Bandung known as shopping and culinary tourism destination. To differentiate Bandung with other destination city in Indonesia, it need a differentiator that will help to characterize the city. A character design that used as a soft tourism campaign is needed. It will become the ambassador to persuade the target market to come and love Bandung as a city tourism destination. First of all, mascot will be a good way to represent and branding the city. The mascot should be developed to represent a culture and positive image of the city and become the pride for its citizens. Object of this study was Cepot from wayang golek Sunda. The Research covers visual aspects, philosophical and ideological. Every character designs are influenced by the culture. Each culture has different visual traditions with different ideological backgrounds. The best approach before make a character design, is to recognize the character design in every culture. How a culture affect the human figure and its visual style and the living creatures. The character culture can be found in its design history, anatomy and story. It become the basis of the new character creation.Â